Climate-smart agriculture and technical efficiency of smallholder maize farmers in Wa East District of Ghana - Adnaan Ibrahim; Benjamin Anang; Lea Anzagra; Emmanuel Derbile (Asia Pacific Network for Sustainable Agriculture, Food and Energy Network (SAFE Network), 2025)
Climate-smart agriculture (CSA) seeks to improve adaptation and mitigation to climate change and eventually, improve the productivity and sustainability of farming. However, CSA adoption particularly among smallholder farmers in developing countries remains low in spite of its potential benefits of improving productivity. Also, empirical evidence of the linkage between CSA adoption and technical efficiency (TE) of smallholder farmers remains scanty. This study therefore examined the drivers of adoption of CSA practices (CSAPs) and how adoption intensity affects TE of smallholder maize production in Wa East District of Ghana. Relying on survey data, generalized Poisson regression and stochastic frontier analysis, the study observed that uptake of multiple CSAPs increased TE of maize producers. The study therefore recommends the provision of CSA training and awareness creation to encourage uptake of multiple CSAPs to increase TE of smallholder maize producers.